Clinical Characteristics and Prognosis of Sepsis Subphenotypes Identified by Coagulation Indicator Trajectories: A Single-Center Retrospective Study - Wang, Bo-yang; Liu-fu, Rong; Dong, Run; Chen, Yan; Wu, Yao; Zhao, Xiao-jun; Sun, Ya-li; Du, Bin; Weng, Li (Thrombosis and Haemostasis, 2025)
This study aimed to identify new sepsis subphenotypes on the basis of coagulation indicator trajectories and comprise clinical characteristics and prognosis.This retrospective study included patients diagnosed with sepsis admitted to the intensive care unit of Peking Union Medical College Hospital from May 2016 to March 2023. Using group-based trajectory models, we classified patients into different subphenotypes on the basis of the dynamic daily changes in coagulation parameters within the first 7 days after sepsis diagnosis. Clinical characteristics and outcomes of patients were compared between subphenotypes.A total of 3,990 patients diagnosed with sepsis were included in this research. Patients were divided into four trajectory groups on the basis of indicator trajectory: Group 1 (n = 500), with high prothrombin times (PTs) and rapidly increasing D-dimer levels; Group 2 (n = 1,334) had normal PT, mildly increasing D-dimer levels and platelet counts. Group 3 (n = 1,013), with mildly elevated PT and D-dimer levels, along with lower platelet counts and fibrinogen levels. Group 4 (n = 1,143) had mildly elevated PT and D-dimer levels along with elevated platelet and fibrinogen levels. Four trajectory subphenotypes exhibit different 28-day mortality, overall in-hospital mortality, bleeding and thrombosis incidence, and the rate of patients with mechanical ventilation.Coagulation trajectory subphenotypes offer a novel approach for stratifying sepsis heterogeneity, identifying high-risk patients, and refining prognostic assessment. The subphenotype with rapidly rising D-dimer levels warrants heightened clinical vigilance due to its association with the poorest outcomes.
Keywords: sepsis; subphenotype; disseminated intravascular coagulation; D-dimer; group-based trajectory models